FUNGSI PRAGMATIK METAFORA DALAM WACANA SURAT PEMBACA BERBAHASA INDONESIA - Deli Nirmala (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2012)
This study aims to describe the pragmatic functions of metaphors in the discourse of letters to the editor in Indonesian. The data were collected through non-participant observations using a note-taking technique. They were analyzed using referential, distributional, introspective, reflexive, and abducting inference techniques. The findings show that the metaphors in the discourse of letters to the editor show assertive, directive, and expressive pragmatic functions. Such functions indicate indirectness of meanings in metaphorical expressions. The indirectness of meanings shows the writers’ politeness strategies to maintain good relations with the readers. The writers give freedom to the readers to agree or disagree with the proposed discourse.